Determination of nutrient composition of some selected traditional home- made meals commonly consumed in Syria - Sarem, Zeinab; Alkhatib, Waad (The North African Journal of Food and Nutrition Research, 2024)
Background: Modifying lifestyles through healthy dietary choices, enhanced cooking skills, and improved nutritional knowledge has been established as an effective strategy for reducing obesity and associated chronic diseases. Aims: This study aims to contribute to this effort by investigating the nutritional profiles of commonly consumed Syrian home-cooked meals. The primary objective was to analyze the macronutrient composition (carbohydrates, protein, fat) of five selected Syrian dishes and compare them to a frequently consumed, plant-based modern meal component. Additionally, the study aimed to assess the contribution of these nutrients to daily dietary needs.Methods:  Four traditional Syrian vegetarian mixed dishes (grape leaves stuffed with rice, rice with pea broth, bulgur with chickpeas and pasta with tomato sauce) were selected for analysis. These were compared to a modern, plant-based food component (fried potatoes). Proximate analysis, based on standard methods established by the Association of Official Analytical Chemists (AOAC), was used to determine the content of macronutrients. Carbohydrate, protein, and fat exchanges for each meal were calculated using a rounding-off method.Results:  All tested traditional dishes exhibited low energy density, with moisture content ranging from 63.16 – 75,63% and ash content ranging from 0.49 – 1.01% ash. Macronutrient compositions revealed carbohydrate contents between 17.43 – 25.41%, fat contents between 0.2 – 2.84%, and protein contents between 2.34 -3.83%. Crude fiber content ranged from 0.15 – 2.17%, and energy density varied from 0.96 – 1.44 Kcal/g. These traditional dishes contributed (63.04 – 75.26%) of total food energy from carbohydrates, (6.48 – 13.85%) from fat and (1.25 – 23.11%) from protein. In contrast, fried potatoes, the modern meal component, displayed medium energy density (1.83 kcal/g), with a distinct macronutrient profile: 60.22% carbohydrate, 1.44% ash, 24.56% fat, 7.26% protein, 4.90% crude fiber, and 1.62% moisture. The energy contribution of fried potatoes was 53.63% from carbohydrates, 35.67% from fat, and 10.70% from protein.Conclusion:  This study provides valuable data for the potential development of a Syrian Food Database. The results suggest that incorporating popular Syrian traditional dishes into healthy dietary intervention programs holds promise for promoting better nutrition.Keywords:  Nutrient composition; Proximate analysis; Syria; Traditional dishes; Food exchange